Struktur, Perilaku, dan Kinerja Pemasaran Cabe Jamu di Kecamatan Bluto - Uswatun Hasanah; Mardiyah Hayati (Jurnal Ilmu Pertanian Indonesia, 2024)
Java long pepper (Piper retrofractum Vahl.) is a potential export commodity. One of the centers of Java long pepper production in Indonesia is Sumenep Regency. However, in marketing, farmers only act as price takers, and prices fluctuate a lot. This study aimed to describe the structure, conduct, and performance of the Java Long Pepper market in Bluto District, Sumenep Regency. Sampling was carried out using the snowball sampling method to obtain a sample of 31 farmers, 2 small traders, and 1 large trader. The analysis technique used is the SCP (structure, conduct, and performance) with qualitative and quantitative approaches. Market structure is analyzed by calculating CR and IHH, market conduct by analyzing pricing methods, marketing channels, and marketing functions, and market performance by marketing margin and farmer’s share. Based on the research results, it is known that the market structure that occurs is an oligopsony with a high concentration and collusion price leadership types by the dominant firm. Market conduct shows that farmers cannot bargain, and traders determine absolute prices. Market performance is seen from marketing channel I which is considered the best, with a marketing margin IDR2.000,00 and a farmer’s share of 97.30%. This condition of imperfect market competition needs to be controlled and paid attention to so that it can be managed well, create healthy business conditions, and avoid monopoly. Keywords: Java long pepper, market performance, market conduct, market structure